2018
DOI: 10.12685/jbab.2017.117-139
|View full text |Cite
|
Sign up to set email alerts
|

Die spätantike Gräbergruppe Basel-Waisenhaus

Abstract: Im Jahr 2010 wurde bei Bauarbeiten im Areal des Basler Waisenhauses eine kleinere Gruppe von Gräbern entdeckt, die anhand von wenigen Beigaben mit einiger Wahrscheinlichkeit in das zweite Viertel des 5. Jahrhunderts datiert. Mit dem Fund dieser Gräber liegt für die Epoche der Spätantike in Basel erstmals eine Gruppe von Bestattungen vor, die eine zivile rechtsrheinische Siedlungstätigkeit ausserhalb der bekannten Befestigungsanlagen in der ersten Hälfte des 5. Jahrhunderts anzeigt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The early medieval period provides even less direct evidence for settlements, consisting mostly of pottery fragments. Based on this, a potential settlement could be reconstructed in the area between the Burgweg and the Alemannengasse [55] as well as between the Mittlere Bru ¨cke and the Wettsteinbru ¨cke [55,56]-though these settlement records were mostly dated between the 7 th and the 9 th century AD. Moreover, an increase in agricultural activities in the region can also be deduced from the botanical remains of the middle of the 7 th century AD onwards, which is traditionally explained by population growth [18,45,46].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The early medieval period provides even less direct evidence for settlements, consisting mostly of pottery fragments. Based on this, a potential settlement could be reconstructed in the area between the Burgweg and the Alemannengasse [55] as well as between the Mittlere Bru ¨cke and the Wettsteinbru ¨cke [55,56]-though these settlement records were mostly dated between the 7 th and the 9 th century AD. Moreover, an increase in agricultural activities in the region can also be deduced from the botanical remains of the middle of the 7 th century AD onwards, which is traditionally explained by population growth [18,45,46].…”
Section: Plos Onementioning
confidence: 99%
“…Few graves from the Petersgasse could also belong to this period [54,58]. A recent study revealed that people were also buried between 370 and 415 AD at Basel-Waisenhaus (n = 11) [40,56]. This small burial group is not only located just in front of the Mu ¨nsterhu ¨gel on the northern riverbank, but also less than 200 m to the east of the munimentum.…”
Section: Late Antique and Early Medieval Gravescapesmentioning
confidence: 99%
“…Moreover, the traditional narratives of the Migration period derived from written sources still hold sway over the interpretation of the archaeological records at Basel, where the burial grounds (including the Basel-Waisenhaus site presented in this study and described in the Data S2 ) were associated with specific ethnic groups. 20 , 21 , 22 , 23 However there has been recent work within Early Medieval archaeological research to revise the hitherto predominant comparison of ethnicity and material culture. 1 , 7 , 8 , 9 , 10…”
Section: Introductionmentioning
confidence: 99%
“…This combination of methods fosters the understanding of local to supra-regional mobility patterns and socio-economic organization in a highly dynamic period of socio-cultural development.
Figure 2 Plan of the burial ground with information about sex, age, grave goods, and the material available for the isotope and aDNA-analyses Modified by M. Depaermentier after Baumann et al., 20 Figure 7 . Images of grave goods by Archäologische Bodenforschung Basel-Stadt.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation